Odpowiedzi

2010-02-02T16:26:50+01:00
A) 3b+(b+1)=3b+b+1=4b+1
b) 5a-(a+1)=5a-a+1=4a+1
c) 2x-(3-5-x)=2x-(-2)-x=x+2
d) 4a-(2-x)=4a-2-x=3a-2
2010-02-02T16:28:45+01:00
A)3b+(b+1) = 3b + b + 1 = 4b + 1
b)5a-(a+1) = 5a - a +1 = 4a +1
c)Tu niewiem czy dobrze rozwiąże bo nie napisałaś gdzie się zaczyna nawias
c)2x-93-5-x) = 2x - 93 - 5 -x = x - (-98) = x + 98
d)4a-(2-x) = 4a - 2 - x = 4a - x - 2
Najlepsza Odpowiedź!
2010-02-02T16:32:05+01:00
A)3b+(b+1)=3b+b+1=4b+1
b)5a-(a+1)=5a-a-1=4a-1
c)2x-<chyba powinien być nawias a nie 9>to jeszcze raz: 2x-(3-5-x)=2x-3+5+x=3x=2
d)4a-(2-x)=4a-2+x